2020
DOI: 10.3346/jkms.2020.35.e200
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Cardiac Radiation to Control Ventricular Tachycardia and Fibrillation Storm in a Patient with Apical Hypertrophic Cardiomyopathy at Burnout Stage: Case Report

Abstract: Stereotactic cardiac radiation for ablation (radioablation) of life-threatening ventricular arrhythmia was recently introduced into clinical practice. A 76-year-old male patient with apical hypertrophic cardiomyopathy at burnout stage, who received defibrillator implantation for the secondary prevention of sudden arrhythmic death, was admitted for repeated defibrillator therapy. Radiofrequency catheter ablation was unsuccessful due to the induction of ventricular fibrillation (VF) and hemodynamically unstable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The treatment was effective for 6 months, after which permanent atrial fibrillation developed and the patient was further treated with pharmacotherapy. The most recent case report by Park et al [ 25 ] describes a life-saving scenario in which STAR was applied for apical hypertrophic cardiomyopathy at a burnout stage. The patient presented hemodynamically unstable sustained monomorphic VT, and the radiofrequency catheter ablation was unsuccessful due to the induction of VF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment was effective for 6 months, after which permanent atrial fibrillation developed and the patient was further treated with pharmacotherapy. The most recent case report by Park et al [ 25 ] describes a life-saving scenario in which STAR was applied for apical hypertrophic cardiomyopathy at a burnout stage. The patient presented hemodynamically unstable sustained monomorphic VT, and the radiofrequency catheter ablation was unsuccessful due to the induction of VF.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the authors performed a secondary review of the bibliographies of the original articles and reviewed articles which referenced the selected papers. Finally, a total of 17 original articles regarding clinical applications of STAR were referenced in the review, including 11 case reports [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], 4 case series [ 10 , 12 , 34 , 35 ], and 2 clinical trial reports [ 11 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although several study results have shown significant improvement in cardiac function with no VT recurrence in the short-term, long-term follow-up results and research on the mechanism by which high-energy rays eliminate the arrhythmia are lacking. Furthermore, despite individual cases having reported PTV maximum doses exceeding 30 Gy and different fractional patterns such as 24 Gy/3 fractions, the most widely used prescription is a single-fraction of 25 Gy (8)(9)(10)(11). In terms of protecting the OARs from radiation, SBRT used for arrhythmia treatment is implemented as single-fraction high-dose radiotherapy for which there is no uniform reference regarding the relative biological effectiveness.…”
Section: A B Cmentioning
confidence: 99%
“…These works report a marked reduction in VT burden [6,7], a decrease in antiarrhythmic drug use [7], and improvement in quality of life [7]. Since then, several centres have reported their early experience with this technique [8] with both positive [9][10][11] and negative [12] results. In this report, we add to the limited evidence detailing our experience with 2 patients for StAR for VT at the ------------------.…”
Section: Introductionmentioning
confidence: 99%